The Urgency of Needs-Based Training Programs in Determining The Training and Education That Will Be Given to Training Participants - Safitri, Winda (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research is motivated by the fact that there are still many training and education programs that still fail to identify the needs of the training participants themselves. This is indicated by the fact that many training participants are still unable to apply the results of the training after attending the training. Therefore, according to researchers, it is very suitable to carry out an assessment of needs-based training programs. Based on the type of training, namely needs-based training, before the training is carried out, a needs analysis must first be carried out so that the training program that will be implemented is in accordance with the needs of the training participants. The type of research is literature study research, with research techniques namely using literature review techniques on previous articles. The research results show that 1) based on the type of training program we can see that before carrying out training, it is necessary to first identify needs so that the training program to be implemented is in accordance with the needs of the community. 2) by identifying needs, the training can run as it should, and the results of the training also have benefits for the training participants.